"I will never be Spanish enough". Gender-based Islamophobia in Spain: socio-educational aspects. - Navarro-Granados, María; Cruz-González, Cristina; Abderrahaman Mohamed, Hallar; Llorent-Bedmar, Vicente (Journal of Gender Studies, 2025)
Recent studies have highlighted that Muslim women, as the most likely recipients of Islamophobia, are uniquely vulnerable to this complex phenomenon. In Spain, these are still very incipient, and practically non-existent from a socio-educational approach. Based on the life stories of 10 Muslim women, this research analyses in depth their experiences with gender-based Islamophobia in the Spanish context, and how it influences their processes of identity construction, feelings of belonging and religiosity. The sample includes Moroccan women, women of Moroccan origin (belonging to the so-called second generation) and converts. Four main thematic blocks emerged from the analysis: identity/feeling of belonging, religiosity, Islamophobia and education. In the discourses analysed, the hijab emerges as a key element of empowerment for many of them. In a context where Islam is often presented as incompatible with Western values, the analyses revealed how the participants experience continuous identity contradictions, producing both a rejection of their culture and roots, and a greater identification with it, sometimes in a reactive way. We argue that it is important for educational and social institutions to address the stereotypes and prejudices associated with Muslim women and to promote the positive construction of multiple, positive and non-exclusive identities.